Model Bisnis Berkelanjutan dan Isu Strategi Pengembangan Model Bisnis Berkelanjutan pada UKM: Tinjauan Literatur Sistematis - Sebrina, Nurzi; Masdupi, Erni; Syahrizal, Syahrizal (Ekonomis: Journal of Economics and Business, 2024)
The United Nations established the Sustainability Development Goals (SDGs) in 2015 as the 2030 Sustainability Development Agenda, which provided a comprehensive framework to guide global efforts toward a more sustainable and inclusive future while addressing socioeconomic and environmental issues. As a result, businesses, particularly small and medium-sized enterprises (SMEs) as part of large corporations, are intensely interested in transforming business models towards sustainability. This article investigates the development of articles on sustainable business models (SBM), specifically SBM in SMEs. The study was conducted using articles obtained from the Elsevier Scopus database.The analysis was carried out using bibliographic research techniques using VOSviewer software and content analysis. Based on the study conducted, it was found that SBM had been discovered between 2002 and 2003, although relatively few articles about business models were found, namely 827 out of 16,784 business model documents. Meanwhile, there are far fewer Scopus documents on SBM for SMEs, namely 19 articles, most of which are systematic literature reviews and case studies. Content analysis shows that SBM in SMEs needs to consider adaptation to uncertain environmental and institutional contexts. Regarding strategic content, the need to maintain symbiotic relationships with stakeholders, founder values, social and environmental values, leadership, value-based competencies, and manager commitment is essential for SBM. Developing a sustainable business model for SMEs is carried out by integrating sustainability into its value chain.